Temporary employment in the practice of Labour Inspection - Górski, Dariusz (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
The article written by a representative of the National Labour Inspectorate presents infringements of regulations exposed during inspections and examples of circumvention of the applicable legal regulations which misinterpret the nature of temporary employment, with particular focus on outsourcing bearing the characteristics of temporary employment. The author analyses the reasons of negative phenomena on the temporary employment market, discusses the procedures used by labour inspectors when finding violations of provisions in this area, and also indicates proposals for changes in the applicable law that would facilitate the National Labour Inspectorate to combat the irregularities revealed and could contribute to restoring the proper meaning of temporary work, in accordance with its essence.  Such proposals include, the possibility for labour inspectors to issue administrative decisions establishing the existence of an employment relationship between a person performing temporary work and the employer-user and introducing consequences in the form of removing the entity from the register of employment agencies in the case of outsourcing in fact being temporary employment.